DISCIPLINARY LIABILITY IN CONNECTION WITH THE EMPLOYEE’S GUILTY ACTIONS (Journal of actual problems of jurisprudence, 2024)
This research provides a detailed comparative analysis of the number of labor disputes and the evolution of Kazakhstan’s labor discipline legislation.  Key observations include the correlation between stringent disciplinary norms and reduced unemployment, the influence of judicial practices on labor discipline, and the necessity of balancing strict discipline with fair treatment to prevent legal disputes. The findings offer valuable insights for optimizing labor policies to support sustainable labor market development in Kazakhstan. These insights align with the goals of SDG 8, which promotes sustained, inclusive, and sustainable economic growth, full and productive employment, and decent work for all.The purpose of this paper is not only to analyze the current state of the labor market in Kazakhstan but also to propose recommendations for optimizing labor policy, taking into account both current challenges and potential opportunities for sustainable development of the labor market   in the country. Based on a wide range of data, including statistical indicators range of unemployment levels, legislative changes, and analysis of judicial practice, we aim to identify correlations and cause-and-effect relationships between labor discipline and market indicators.Keywords: employee, employer, labor, labor law, employment contract, termination of employment contract, labor relations, labor disputes, dismissal, at the initiative of the employer.